Human rights in higher education and its application in the social environment - Vázquez Luna, Elio Francisco; Amador Corral, Sandra Rubí; Escalera Silva, Luz Alejandra
In order to identify the importance for teachers of teaching human rights in higher education to apply them to their social environment, a quantitative study was carried out analyzing teaching styles and pedagogical models. The sample was made up of professors from the social sciences area of the Emiliano Zapata University who taught the subject. Among the main results, it was found that 91% of teachers are concerned about the way in which they can help students learn and consider the subject as a fundamental basis for their professional practice. In addition, 90% consider that knowledge of the subject can guide students to solve some problems in their daily lives. 100% consider that their professional experience can help students understand the content of the subject (autocratic model); 91% are interested in knowing what and how students learn (democratic style); 66% consider that the knowledge acquired during the teaching of my subject on human rights (laissez-faire style) is not the responsibility of the students. In conclusion, the teachers consider that their knowledge is very important and they believe that the interaction between teachers and students, as well as the opinion of the students, are paramount; The learning that the student has must serve to interpret reality and have as a consequence a mental change and they agree that the family and society are an important part of the teaching-learning process.